Combustion, cofiring and emissions characteristics of torrefied biomass in a drop tube reactor. (August 2015) - Ndibe, Collins; Maier, Jörg; Scheffknecht, Günter
Abstract: The study investigates cofiring characteristics of torrefied biomass fuels at 50% thermal shares with coals and 100% combustion cases. Experiments were carried out in a 20 kW, electrically heated, drop-tube reactor. Fuels used include a range of torrefied biomass fuels, non-thermally treated white wood pellets, a high volatile bituminous coal and a lignite coal. The reactor was maintained at 1200 °C while the overall stoichiometric ratio was kept constant at 1.15 for all combustion cases. Measurements were performed to evaluate combustion reactivity, emissions and burn-out. Torrefied biomass fuels in comparison to non-thermally treated wood contain a lower amount of volatiles. For the tests performed at a similar particle size distribution, the reduced volatile content did not impact combustion reactivity significantly. Delay in combustion was only observed for test fuel with a lower amount of fine particles. The particle size distribution of the pulverised grinds therefore impacts combustion reactivity more. Sulphur and nitrogen contents of woody biomass fuels are low. Blending woody biomass with coal lowers the emissions of SO2 mainly as a result of dilution. NOX emissions have a more complex dependency on the nitrogen content. Factors such as volatile content of the fuels, fuel type, furnace and burner configurations also impact the final NOX emissions. In comparison to unstaged combustion, the nitrogen conversion to NOX declined from 34% to 9% for air-staged co-combustion of torrefied biomass and hard coal. For the air-staged mono-combustion cases, nitrogen conversion to NOX declined from between 42% and 48% to about 10%–14%. Highlights: Impact of torrefaction on cofiring was studied at high heating rates in a drop tube. Cofiring of torrefied biomasses at high thermal shares (50% and higher) is feasible. Particle size impacts biomass combustion reactivity more than torrefaction. In a drop tube reactor, torrefaction has no negative impact on combustion reactivity. Air-staging can successfully reduce NOX during cofiring of torrefied biomasses.